A Study of the Relationship between Blood Glucose and Serum Insulin in Acute Cerebrovascular Disease. (1st August 2022) - Zhao, Lei; Xiu, Shuangling; Sun, Lina; Mu, Zhijing; Fu, Junling
Abstract : Objective . The objective of this study was to examine the correlation between blood glucose and serum insulin with acute cerebrovascular disease. Methods . A total of 1548 patients with acute cerebrovascular illness and 364 patients with a normal physical examination who were admitted to our hospital (endocrinology department) between January 2017 and July 2020 were recruited. Patients with acute cerebrovascular illness were included in the experimental group, while healthy individuals after physical examinations were included in the control group. All patients' blood glucose and serum insulin levels were measured, and the association of blood glucose and serum insulin with acute cerebrovascular illness was investigated. Results . Acute cerebrovascular disease is associated with significantly higher blood glucose and serum insulin levels versus healthy status (P < 0.05 ). Blood glucose and serum insulin levels were observed to be significantly higher in the hemorrhagic stroke group than in the ischemic stroke or mild hemorrhagic group (P < 0.05 ). Severe ischemic strokes were associated with significantly higher blood glucose levels versus mild ischemic strokes (P < 0.05 ). There were no significant differences in serum insulin levels between the severe ischemic stroke group and the mild ischemic stroke group (P > 0.05 ). Conclusion . A rise in blood glucose and serum insulin levels is associated with the incidence and prognosis of acute cerebrovascular disease, and it is positively correlated with the severity of the acute cerebrovascular disease.